Economic intelligence and its role in the competitiveness of major countries (USA, Japan, France) - Nasreddine, Derkaoui; Nafisa, Nasri (International journal of economic perspectives, 2025)
The ability to gather information, understand economic events, analyze them, and make sound economic decisions, as well as handle the collection and analysis of economic data in a logical and scientific manner, and comprehend and apply economic theories in practice, constitutes economic intelligence. This productive approach, heavily influenced by American management schools, now represents a constrained view of reality, where defending economic interests has become the central focus of U.S. strategy. President Bill Clinton gave a global dimension to the economic intelligence process. Therefore, we believe it is useful to broaden the analysis by presenting the historical context of the concept. Arab countries have not fully adopted this approach or integrated it into their scientific and economic fields... etc. Economic intelligence is considered an integral part of research and knowledge activities, encompassing vigilance, early warning, analysis, summarization, impact assessment, and counteraction. Its primary goal is to protect the national heritage, especially in its technological and industrial dimensions.